School, Community, and Church Activities: Relationship to Academic Achievement of Low-Income African American Early Adolescents in the Rural Deep South - Mathew J. Irvin; Thomas W. Farmer; Man-Chi Leung; Jana H. Thompson; Bryan C. Hutchins (Journal of Research in Rural Education, 2010)
The relationship of participation in school, community, and church activities to the academic achievement (i.e., end-ofyear school grades) of African American youth in rural low-income communities was examined. Participants included 280 students (177 girls and 103 boys) in the 7th and 8th grades of two public middle schools. Participation in school, community, and church activities was measured by participants' involvement in extracurricular activities in these contexts. Results indicated that after accounting for school activities and other control variables, church activities were related to academic achievement. Findings suggested that it is important to consider participation in the activities of contexts outside of school that may support the achievement of African American youth in the rural Deep South.